What is the equivalent of 27/5 in decimal form?

Answers

Answer 1
Answer: 5.4 is equivalent to 27/5.
Answer 2
Answer:

Answer: 5.4

Step-by-step explanation: 27/5, so 5x5 makes 25 and 2 remaining so 5x0.4=2 so answer is 5+0.4 which equals to 5.4


Related Questions

at a local coffee shop, about 20% of the customers who buy coffee also buy a pastry. if they have 300 customers buying coffee about how many pastries should they expect to sell?
According to a poll, 76% of California adults (385 out of 506 surveyed) feel that education is one of the top issues facing California. We wish to construct a 90% confidence interval for the true proportion of California adults who feel that education is one of the top issues facing California. Find the error bound. (Round your answer to three decimal places.)
Molly is at the Ice Cream Store. To get there, she went 1 unit right and 7 units down. Which location did Molly start from?
a family buys 6 airline tickets online. the family buys travel insurance that costs 18 per ticket. the total cost is 1,044
A preliminary sample of holiday shoppers revealed that the standard deviation of the amount of money they are planning to spend on gifts during the coming holiday season is $80. How many holiday shoppers should be sampled in order to estimate the average amount of money spent on gifts by all holiday shoppers with a margin of error of $7 and with a 99% confidence

Solve for x: 3x − 24 = 81
57/3
105/3
57
105

Answers

To solve for x, we need to get all our constants on one side of the equal sign and all our variables on the other side of the equal sign.


3x - 24 = 81

3x -24 + 24 = 81 +24

3x = 81 + 24

3x = 105

3x/3 = 105 / 3

x = 105 / 3



Answer:

x=(105)/(3)

Step-by-step explanation:

To solve for x, we need to get all our constants on one side of the equal sign and all our variables on the other side of the equal sign.

3x-24=81

3x-24+24=81+24

3x=81+24

3x=105

(3x)/(3)=(105)/(3)

Therefore, the answer is:x=(105)/(3)

What should be done to both sides of the equation in order to solve -5m=-40

Answers

Answer:

divide each side by -5

Step-by-step explanation:

-5m = -40

divide each side by -5

-5m/-5 = -40/-5

m = 5


Hello, there!

Answer:

m=8 or 8=m

*The answer must have a positive sign.*

Step-by-step explanation:

First, you had to divide by -5 from both sides of an equation.

(-5m)/(-5)=(-40)/(-5)

And, then simplify and solve equation.

40/5=8

m=8

Hope this helps!

Which of the following is equivalent to 18 minus StartRoot negative 25 EndRoot?

Answers

Answer:

18-5i

Step-by-step explanation:

Answer: 12-i

               12-(√-1)

Step-by-step explanation:

18-√(-25)   Original Question

18-(√(25) * √(-1) )   Split

18-5*(√(-1) )   Solve for square root

12-√(-1)   Subtract

You can substitute √(-1) for i

12-i   Substitute

An oil company fills 1/12 of a tank in 1/3 hour. At this rate, which expression can be used to determine how long will it take for the tank to fill completely? a. 1/12 x 3 hours
b. 1/3 x 12 hours
c. 1/3 x 1/12 hour
d. 3 x 12 hours

Answers

Selection B is appropriate.

_____
It takes 12 times as long to fill the whole tank as it does to fill 1/12 of the tank.
.. 12 * (1/3 hour) = (1/3)*12 hour

Answer: b . (1)/(3)*12 hours

Step-by-step explanation:

Given : A oil company fills (1)/(12) of a tank in (1)/(3) hour.

i.e. Time taken to fill (1)/(12) of a tank=  (1)/(3) hour.

By using the Unitary method, we multiply 12 on bith the sides of the above expression we get

Time taken to fill (1)/(12)*12  tank=  (1)/(3)*12 hour.

⇒ Time taken to fill 1 tank=  (1)/(3)*12=4 hour.

Hence, it will take (1)/(3)*12 hours or 4 hours for the tank to fill completely.

Thus , the correct answer is b . (1)/(3)*12 hours

Find the product 8x(2x^2+8x-5)

Answers

Answer:

  16x^3 +64x^2 -40x

Step-by-step explanation:

Use the distributive property. The factor outside parentheses multiplies each term inside parentheses:

  8x(2x^2 +8x -5) = (8x)(2x^2) +(8x)(8x) +(8x)(-5)

  = 16x^3 +64x^2 -40x

What is (7p + 6) - (9p - 7)?

Answers

Answer:

-2p +13

Step-by-step explanation:

(7p + 6) - (9p - 7)

Distribute the minus sign

(7p + 6) - 9p + 7

Combine like terms

7p -9p   +6 +7

-2p +13

Answer:

-2p + 13

Step-by-step explanation:

Distribute the -1 to (9p - 7):

7p + 6 - 9p + 7

Add like terms (7p and -9p, 6 and 7):

-2p + 13